Extended preoperative polyvinyl alcohol microembolization of intracranial meningiomas: assessment of two embolization techniques. - Wakhloo, A K; Juengling, F D; Van Velthoven, V; Schumacher, M; Hennig, J; Schwechheimer, K (American Journal of Neuroradiology, 1993)
PURPOSE To evaluate the efficacy of preoperative meningioma devascularization with small polyvinyl alcohol (PVA) particles.METHODS In 34 patients with intracranial meningiomas, CT, MR, 1H MR spectroscopy, MR volumetric measurements, intraoperative ultrasound, and histopathologic findings were used to compare the efficacy of two embolization techniques: 1) administration of 150- to 300-microns PVA particles in the usual suspension, and 2) administration of 50- to 150-microns PVA particles in a highly diluted suspension.RESULTS Angiography after embolization demonstrated the total elimination of tumor blush in all patients. Contrast-enhanced MR after the administration of 150- to 300-microns PVA particles revealed a reduction of tumor enhancement in only two out of 14 patients. Only after the use of small particles could significant tumor necrosis be depicted on MR and confirmed histopathologically after surgery. In 12 of 20 patients, 30% to 95% of the whole tumor was necrotic with 17% to 20% reduction of tumor volume in four cases, leading to recovery from the initial neurologic deficits. In three of 20 patients without sufficient steroid medication before the treatment, tumor swelling occurred. Postembolization MR disclosed a tumor volume increase of 10% to 20% in these patients. 1H MR spectroscopy of the tumors showed an increase of lactate and aliphatic lipid compounds after embolization, indicating tumor infarction. Surgical removal of effectively embolized meningiomas without significant blood loss was possible. The appearance of the tumor at operation, ultrasound examination, and the histopathologic examination of different parts of the tumor confirmed the preoperative MR findings suggesting necrosis.CONCLUSION Extended microembolization with 50- to 150-microns PVA particles improves the surgical treatment of meningiomas, as compared with larger particle embolization. It may also be the only treatment required in older or high-risk patients. The protective effect of steroid medication before the endovascular treatment of meningiomas is suggested by our study.